2017
DOI: 10.4103/ijem.ijem_230_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the cernea classification of external branch of superior laryngeal nerve in relation to the ultrasound-based volume of thyroid gland

Abstract: Introductíon:Goiter is a very common problem dealt with by surgeons. Surgical treatment of thyroid requires removal of a part (hemi) or whole of the gland (total thyroidectomy). The external branch of the superior laryngeal nerve (EBSLN) is an important but less researched structure to be preserved during surgery. Various studies have described the incidence of different types of EBSLN, but have not described regarding the relationship between the change in volume of the gland to the nerve.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Therefore, on the basis of our results in primary thyroid surgery, functional identification rates of the EBSLN could exceed 95% due to appropriate anatomical dissection and proper use of electrophysiological monitoring. Previous studies have reported the successful identification of the EBSLN with the assistance of IONM [118192021222627]. After significant advances and improvements in anatomical knowledge, surgical technique, and electrophysiological monitoring, the EBSLN identification rate has been reported to reach more than 90% in recent studies [34222328].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, on the basis of our results in primary thyroid surgery, functional identification rates of the EBSLN could exceed 95% due to appropriate anatomical dissection and proper use of electrophysiological monitoring. Previous studies have reported the successful identification of the EBSLN with the assistance of IONM [118192021222627]. After significant advances and improvements in anatomical knowledge, surgical technique, and electrophysiological monitoring, the EBSLN identification rate has been reported to reach more than 90% in recent studies [34222328].…”
Section: Discussionmentioning
confidence: 99%
“…The EBSLN comes into play at frequencies above 150 Hz, thus it is particularly involved in producing the high tones. This can be predominantly significant for individuals using their voice professionally[ 13 ]. In case of thyroidectomy STA must be ligated and is highly essential to ensure proper hemostasis[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even for non-professionals, the perception of an abnormal voice impairs the quality of life and decreases the general health in many ways and affected patients may be unable to shout for help[ 15 ]. The incidence of EBSLN injury in patients undergoing thyroidectomy is reported to be up to 58%[ 13 , 15 , 18 ]. One of the earlies reported case goes back to 1935 when the famous opera singer Amelita Galli- Curci suffered from damage to the EBSLN after thyroid surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies conducted by Ravikuvar et al,[ 20 ] a significant relationship between the incidence of Cernea type 2b and goiter with a volume greater than 50 cc (Odd ratio: 438.5 (95% CI: 194.63-988.28) and the presence of hyperthyroidism (Odd ratio: 6.425 (95% CI: 2.835-14.562)) was detected, while there was no significant relationship concerning age and sex. 180 of 912 thyroid lobes evaluated in this study were larger than 50 cc in volume (19.7%) and 82.2% of large lobes were toxic.…”
Section: Discussionmentioning
confidence: 93%